Strategi Peningkatan Performa Wasit di Asosiasi Pssi Kota Cimahi - Mubarok, Irfan; Husdarta, J.S; Syamsudar, Bangbang (Peneliti.net, 2024)
The background of this thesis is that the performance of a referee is an inseparable part of a match, the good and bad of a match can be seen from the quality of the performance of the match officials who run it. Good referee performance is expected to give the best performance by players. Performance as a record produced on a particular job or activity over a period of time.